1995
DOI: 10.1002/1520-6807(199507)32:3<210::aid-pits2310320308>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing attention deficit hyperactivity disorder symptoms utilizing an automated classroom reinforcement device

Abstract: Psychologists and physicians are frequently approached by parents and, indirectly, by classroom teachers to diagnose and treat Attention Deficit Hyperactivity Disorder. Requests are also frequently made for psychostimulant medication to control ADHD behavioral symptoms. One reason for such requests is that alternative classroom approaches to treating ADHD have focused on positive reinforcement, response cost, and token reinforcement programs, all of which can require extensive teacher involvement. One of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The ATS is extremely easy to use and appears to require little change in classroom routines. Initial research conducted in special after-school pro-grams (Gordon, Thomason, Cooper, & Ivers, 1991) and in self-contained behavior management classrooms (DuPaul, Guevremont, & Barkley, 1992;Evans, Ferre, Ford, & Green, 1995) has found it to be quite effective, and a recent study in two regular education classrooms found similar results (Polaha & Allen, 2000).…”
Section: Consequent Eventsmentioning
confidence: 94%
“…The ATS is extremely easy to use and appears to require little change in classroom routines. Initial research conducted in special after-school pro-grams (Gordon, Thomason, Cooper, & Ivers, 1991) and in self-contained behavior management classrooms (DuPaul, Guevremont, & Barkley, 1992;Evans, Ferre, Ford, & Green, 1995) has found it to be quite effective, and a recent study in two regular education classrooms found similar results (Polaha & Allen, 2000).…”
Section: Consequent Eventsmentioning
confidence: 94%
“…Deficits in children's attention are problems in facilitating, sustaining, or disengaging these relationships apart from the specific environmental event. Thus, attentional problems may be deficits in sustaining or disengaging the behaviors in relation to the environment (Barkley, 1994; (Drewe, 1975 (Barkley, 1990;Braswell & Bloomquist, 1989;Reid & Harris, 1993) and, more recently, the development of attention-training strategies (Sohlberg & Mateer, 1987; Thomson, 1994;Williams, 1987 (Pfiffner & Barkley, 1990;Pfiffner & O'Leary, 1987;Rosen, O'Leary, Joyce, Conway, & Pfiffner, 1984), response cost (Atkins, Pelham, & White, 1990;Cocciarella, Wood, & Low, 1995;DuPaul, Guevre-mont, & Barkley, 1992;Evans, Ferre, Ford, & Green, 1995;Gordon, Thomason, Cooper, & Ivers, 1991;Rapport et al, 1987), home-school contingencies (Abramowitz & O'Leary, 1991;Kelley & Carper, 1988), and peermediated contingencies (Carden-Smith & Fowler, 1984;Gresham & Gresham, 1982;Lentz, 1988).…”
Section: Disinhibitionmentioning
confidence: 99%
“…Concerning their overall mental process, many ADHD children appear to have low IQs and poor school performance. The use of drugs, such as methylphenidate, dextroamphetamine, and pernoline, improves the performance of children with ADHD in mathematics and working memory (Evans, Ferre, & Green, 1995). Verbal skills of children with ADHD have often been assessed by the WISC-I11 verbal scales since the general mental factor g is highly loaded by four of the five basic Verbal subscales (Vocabulary, Information, Similarities, and Arithmetic) and in only one Verbal subscale (Comprehension) is the Factor g moderately loaded (Karnphaus, 1993).…”
mentioning
confidence: 99%